EXPLORATION STUDY OF MANAGEMENT AND SATISFACTION IN THE UTILIZATION OF WORKSHOP FACILITIES AND INFRASTRUCTURE IN SMK X BANDUNG - Pratama, Alfian Syahbari; Mubarak, Ibnu; Darmawan, Bambang; Noor, Ridwan adam (Journal of Mechanical Engineering Education, 2020)
hisstudyaimsto find out the management and student’s satisfaction in usingfacilities and infrastructure in motorcycle engineering workshops. This research was conducted because when researchers conducted field experience (PPL) activities found that the school management was not maximized, workshop facilities were not appropriate, and the ratio of the number of practical tools to students was not ideal. The method used is descriptive. The head of the workshop and studentsbeing the samplesof SMK X Bandung with the subject of the head of the workshop as many as 1 person and students of class XI as many as 42 students. Data collection techniques using the questionnaire method and observing the workshop facilities and infrastructure, and documentation. Based on explorations that have been carried out in the work area of the engine, chassis, and automotive electrical contacts for electrical contacts the amount does not match the BSNP standard used. Storage room, instructor's work table, chairs, tool cabinets and materials, motorcycle object training facilities, media engine stands, electrical media, Motorcycle Engineering and Business equipment for dial test indicators, workshop support equipment and trolly equipment are not in accordance with BSNP standards used. Data analysis in this study uses descriptive analysis techniques, the analysis uses the percentage of data used to see the comparison of the size of the number of answers given by respondents, because the frequency of respondents' answers for each item is not the same. The results of management research and satisfaction in the utilization of facilities and infrastructure of Motorcycle Engineering workshops are as follows, 1) Management of workshop facilities and infrastructure is included in the excellent category. 2) Student satisfaction in the use itis included in satisfactory category.